Mitochondrial unfolded protein response (UPRmt): what we know thus far - Torres, Angie K.; Fleischhart, Veronika; Inestrosa, Nibaldo C. (Frontiers in Cell and Developmental Biology, 2024)
Mitochondria are key organelles for the optimal function of the cell. Among their many functions, they maintain protein homeostasis through their own proteostatic machinery, which involves proteases and chaperones that regulate protein import and folding inside mitochondria. In the early 2000s, the mitochondrial unfolded protein response (UPR mt ) was first described in mammalian cells. This stress response is activated by the accumulation of unfolded/misfolded proteins within the mitochondrial matrix, which results in the transmission of a signal to the nucleus to increase the expression of proteases and chaperones to address the abnormal mitochondrial protein load. After its discovery, this retrograde signaling pathway has also been described in other organisms of different complexities, suggesting that it is a conserved stress response. Although there are some specific differences among organisms, the mechanism of this stress response is mostly similar and involves the transmission of a signal from mitochondria to the nucleus that induces chromatin remodeling to allow the binding of specific transcription factors to the promoters of chaperones and proteases. In the last decade, proteins and signaling pathways that could be involved in the regulation of the UPR mt , including the Wnt signaling pathway, have been described. This minireview aims to summarize what is known about the mechanism of the UPR mt and its regulation, specifically in mammals and C. elegans.